Sertoli Leydig Cell Tumor of Ovary - Roohi, Mahera (International Journal of Pathology, 2018)
Sertoli-Leydig cell tumor is a group of tumors composed of variable proportions of Sertoli cells, Leydigcells and sometimes heterologous elements. Most tumors are unilateral, confined to the ovaries, and are seenduring the second and third decades of life. These tumors are characterized by the presence of testicularstructures that produce androgens. Hence, many patients have symptoms of virilization depending on the quantityof androgen production.1We are presenting a case of 16 yrs old girl who presented with symptoms of virilization. She was operated for theovarian mass. A diagnosis of sertoli-leydig cell tumor was rendered.